(untitled) (GOING CONCERN : JURNAL RISET AKUNTANSI, 2021)
Fixed assets are one of the important elements for carrying out the operational activities of an organization or government. Therefore, fixed assets must be managed properly. Reliability of fixed asset management, especially management in order to the recognition, measurement and disclosure of fixed assets will also have an effect on the quality of the resulting financial statements. The aim of this research was to determine the suitability of fixed asset management at the Regional Office of the National Land Agency of North Sulawesi Province with the Statement of Government Accounting Standards 07. The results obtained were that the Regional Office of the National Land Agency of North Sulawesi Province had implemented fixed asset management activities in accordance with the Standard Statement Government Accounting 07. However, there is still a lack of information regarding depreciation of fixed assets that has not been disclosed in the financial statements. The Regional Office of the National Land Agency of North Sulawesi Province was expected to improve disclosures about these fixed assets.